Sistem Penjaminan Mutu Sekolah di Indonesia - Muhamad Dini Handoko (Jurnal Dewantara, 2021)
To ensure the implementation of education in accordance with quality standards, it is necessary to continuously and continuously assess the feasibility and performance carried out in order to make improvements and improve the quality of higher education. A policy is always associated with the public. Public policies are decisions that are binding on many people at the strategic or outline level made by public authorities. Performance is an activity that has been achieved by a worker in carrying out the tasks and work assigned to him. The success of quality management in higher education can be measured by the level of customer satisfaction. Higher education can be said to be successful if it is able to provide services according to the expectations of "customers of education" and produce satisfactory products, especially for the public who use educational services.